HIV-RELATED KNOWLEDGE, ATTITUDE AND BEHAVIOR AMONG MALE TO FEMALE TRANSGENDERS: THE CASE OF INDONESIA - Rosyidah, Hanifatur; Mokhtar, Rafidah Hanim Binti; Hidayat, Muhamad Taufik (International Journal of Psychosocial Rehabilitation, 2020)
Male to Female (MtF) transgender persons are called waria in Indonesia. As generally around the world, many waria involved in prostitution which are disclosing them to several high risk behaviours related with Human Immunodeficiency Virus (HIV). The aim of this study was to examine the knowledges, attitudes, and HIV risk behaviours among MtF transgenders in Semarang City, Indonesia. This study employed a validated questionnaire in Bahasa Indonesia to measured knowledges, attitudes, and HIV risk behaviours. With a simple random sampling method, 35 subjects took part in the survey. Data analysis used IBM SPSS statistics. Most of the subjects revealed to have HIV-related sexual risk, eventhough only a quarter were sex workers. Misconceptions still remained among the subjects. Inconsistent condom use was often. Adequate knowledge did result in better attitude towards HIV. However, multiple regression analysis showed that subjects with higher knowledge in HIV tend to have higher sexual risks (β = 0.320, p = 0.030). Educating the MtF transgender community about HIV does not see to adequately reduce the HIV related sexual risks. Raising perception of risk (fear) may be effective to raising awareness of MtF transgenders to eliminate HIV-related high risk behaviours.